Pemberdayaan Perempuan di Kampung Tematik Jamrut melalui Kreativitas Berbasis Ecoprint - Ratieh Widhiastuti; Wisudani Rahmaningtyas; Nina Farliana; Dwi Endah Kusumaningtias (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The COVID-19 pandemic has had a significant effect on the management of the Kampung Tematik Jamrut in particular, and the economic impact on women in the Ngijo Village. Guava and oranges crop that cannot be sold well, require alternative solutions for the use of existing natural resources to create economic product. Providing new skills by utilizing natural materials that are easily available for women in Kampung Tematik Jamrut, Ngijo Village is the goal of community service activities. The solution provided is training and practice of making handicrafts in the form of fabrics with the ecoprint technique. The results of the service showed that the service activities which were divided into four stages, namely socialization, training, practice and evaluation were very well received by the service participants, and the service participants found it useful to be applied in daily life because it was known that some of the participants worked as tailors. The ecoprint technique with the steam method is cheap, easy and simple to practice.